Cyborg athletes: Embracing transhumanism in the remaining modern society - Miah, A. (1999)
This paper argues that transhumanism is met with scepticism, not for it lacking applicability, but for the lack of understanding about how transhumanity can become manifest within a high-technological society. It is considered that the integration of transhuman ideals within social praxis is problematic in a variety of social context, but that sport offers such an example where transhumanism can be applied. Offering a pseudo-natural conception of the human, elite sports embody transhuman values that can promote its application to, otherwise, doubtful cultures. As such, the paper articulates the sporting arena, where the concept of humanness is suitably distorted, and argues that value within sports is afforded by the transhuman qualities of an athlete and their ability to transcend known boundaries of human capability. It is described how sports perpetuate a tendency towards, an endorsement of, and a dependence upon the physical transcendence of humanness. In this respect, sport offers a unique environment where the idea of transhuman can gain social credibility and where its ideal becomes manifest and normalised.